انعكاسات تطورات قطاع النقل البحري على اتجاه حركة التجارة الدولية خلال الفترة 2012-2022 - نصيرة, سباق عبد القادر; وهيبة, زين (جامعة الوادي - University of Eloued, 2023)
".تهدف الدراسة لتسليط الضوء على التطورات الحاصلة في مجال النقل البحري، ومدى انعكاسها على اتجاه حركة التجارة الدولية، سواء بالزيادة أو بالنقصان. حيث توصلت إلى أن النقل البحري المتطور، هو الوسيلة المثالية لإشباع حاجات التجارة الدولية ،باعتباره المساهم الأكبر في زيادة حجم التبادل الدولي، بسبب الأداء العالي، والتكاليف المنخفضة، والسرعة، والأرباح الطائلة، مما يعزز التنمية الاقتصادية للدول ،وعليه توضحت الرؤيا وثبت أن هناك علاقة طردية بين حجم النقل البحري وحجم التجارة الدولية، وهذا ما تم إثباته في الدراسة القياسية وذلك على الرغم من كل الازمات المتتالية التي تعصف بالاقتصاد العالمي، الذي يسبح في بيئة اقتصادية معقدة. ا t. " "Abstract: This study aims to highlight deve loupeurs occuring iu the field of marine trausporation (shipping) and the extent of ist reflection on the direction of interuational trade moveweut, wether by increase or decrease. Where i concluded that advauced warine trans part is the ideal meaus to satisfy the ueeds of the international trade as it is the largest coutrbutor to in crease the volume of inteanational trade exchange due to high pergormance, loue cost, speed and huge profits which enhances the economic deve lopment og countries. Accordingly, the vision becamc clear and it was proven that there is a direct relationship between the volume of maritine transport and the volume of international trade and this was proven in the standard study, despite all the sucossive occupations that afflict the global economy that swims in an comp lex econic environment. The key words: Shipping – interuationational trade- technological development- economical developmen"
Keywords: النقل البحري، التجارة الدولية، التطور التكنولوجي، التنمية الاقتصادية.; Shipping – interuationational trade- technological development- economical developmen